Status, habitat use, and gear-specific conservation of threatened seahorses: The first integrated assessment in Taiwan - Colin Kuo-Chang Wen; Mei Shuet Kong; Ting-Chun Kuo; Chia-Hao Chang; Chih-Yang Huang; Chih-Wei Chen; Graham A. Short; Nathan W. Price (Biological Conservation, 2026)

Deep Convective Activity in Tropical Cyclones and its Impact on Cirrus Clouds: Using Lightning as a Proxy - Joydeb Saha; Ashish Routray; Colin Price; Kieran M. R. Hunt; K. B. R. R. Hari Prasad; Anirban Guha (Pure and Applied Geophysics, 2026)

Reef fish assemblages show limited response to giant clam density and restocking - Nathan W. Price; Yan-Zhen Meng; Wen-Yuan Zhang; Jinn-Shing Weng; Ching-Min Yang; Kao-Sung Chen; Joseph Heard; Wei-Chen Tung; Yu-De Pei; Colin Kuo-Chang Wen (Regional Studies in Marine Science, 2026)

Lightning used to follow ship-tracks in Eastern Mediterranean winter thunderstorms - Yoav Yair; Menahem Kozets; Yanai Namia-Cohen; Colin Price (Atmospheric Research, 2026)

Lightning data assimilation enhances thunderstorm prediction capability - Colin Price (Science Bulletin, 2025)

Declining discount rate, rising non-timber benefits and the optimal sequence of rotations - Colin Price; Rob Willis (Forest Policy and Economics, 2024)

Acute noise is harmful on the anti-predator behaviour of commercially important juvenile coral reef fishes - Nathan William Price; Yijung Liu; Kao-Sung Chen; Cheng-Hao Tang; Chi-Fang Chen; Ming-Chung Cheng; Colin Kuo-Chang Wen (Behavioural Processes, 2023)

Fewer obligate coral-dependent fishes associated with corals covered by coral-killing sponge Terpios hoshinota - Yu-De Pei; Nathan William Price; Joseph Heard; Chieh-Hsuan Lee; Hsuan Tsang; Colin Kuo-Chang Wen (Marine Biology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Scraping and grazing herbivorous/detritivorous fish display opposite feeding behaviours under different protection regulations - Nathan William Price; Kao-Sung Chen; Chaolun Allen Chen; Colin Kuo-Chang Wen (Marine Biology Research, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Glossary on atmospheric electricity and its effects on biology - Pablo Fdez-Arroyabe; Konstantinos Kourtidis; Christos Haldoupis; Snezana Savoska; James Matthews; Lluis M. Mir; Pavlos Kassomenos; Michal Cifra; Susana Barbosa; Xuemeng Chen; Snezana Dragovic; Christos Consoulas; et al. (International Journal of Biometeorology, 2021)

Challenges in coupling atmospheric electricity with biological systems - Ellard R. Hunting; James Matthews; Pablo Fernández de Arróyabe Hernáez; Sam J. England; Konstantinos Kourtidis; Kuang Koh; Keri Nicoll; R. Giles Harrison; Konstantine Manser; Colin Price; Snezana Dragovic; Michal Cifra; et al. (International Journal of Biometeorology, 2021)
The atmosphere is host to a complex electric environment, ranging from a global electric circuit generating fluctuating atmospheric electric fields to local lightning strikes and ions. While research on interactions of organisms with their electrical environment is deeply rooted in the aquatic environment, it has hitherto been confined to interactions with local electrical phenomena and organismal perception of electric fields. However, there is emerging evidence of coupling between large- and small-scale atmospheric electrical phenomena and various biological processes in terrestrial environments that even appear to be tied to continental waters. Here, we synthesize our current understanding of this connectivity, discussing how atmospheric electricity can affect various levels of biological organization across multiple ecosystems. We identify opportunities for research, highlighting its complexity and interdisciplinary nature and draw attention to both conceptual and technical challenges lying ahead of our future understanding of the relationship between atmospheric electricity and the organization and functioning of biological systems.

Natural ELF fields in the atmosphere and in living organisms - Colin Price; Earle Williams; Gal Elhalel; Dave Sentman (International Journal of Biometeorology, 2021)

Zincoberaunite, ZnFe3+ 5(PO4)4(OH)5⋅6H2O, a new mineral from the Hagendorf South pegmatite, Germany - Nikita V. Chukanov; Igor V. Pekov; Ian E. Grey; Jason R. Price; Sergey N. Britvin; Maria G. Krzhizhanovskaya; Anthony R. Kampf; Bernhard Dünkel; Erich Keck; Dmitry I. Belakovskiy; Colin M. MacRae (Mineralogy and Petrology, 2017)

On the Use of VLF Narrowband Measurements to Study the Lower Ionosphere and the Mesosphere–Lower Thermosphere - Israel Silber; Colin Price (Surveys in Geophysics, 2017)

Analysis of G ambierdiscus transcriptome data supports ancient origins of mixotrophic pathways in dinoflagellates - Dana C. Price; Natalie Farinholt; Colin Gates; Alexander Shumaker; Nicole E. Wagner; Paul Bienfang; Debashish Bhattacharya (Environmental Microbiology, 2016)
Summary Toxic dinoflagellates pose serious threats to human health and to fisheries. The genus Gambierdiscus is significant in this respect because its members produce ciguatoxin that accumulates in predominantly tropical marine food webs and leads to ciguatera fish poisoning. Understanding the biology of toxic dinoflagellates is crucial to developing control strategies. To this end, we generated a de novo transcriptome library from G. caribaeus and studied its growth under different culture conditions to elucidate pathways of carbon (C) and nitrogen (N) utilization. We also gathered available dinoflagellate transcriptome data to trace the evolutionary history of C and N pathways in this phylum. We find that rather than being specific adaptations to the epiphytic lifestyle in G. caribaeus , the majority of dinoflagellates share a large array of genes that putatively confer mixotrophy and the ability to use N via the ornithine‐urea cycle and nitric oxide synthase production. These results suggest that prior to plastid endosymbiosis, the dinoflagellate ancestor possessed complex pathways that linked metabolism, intercellular signaling, and stress responses to environmental cues that have been maintained by extant photosynthetic species. This metabolic flexibility likely explains the success of dinoflagellates in marine ecosystems and may presage difficulties in controlling the spread of toxic species.

Effects of Energetic Solar Emissions on the Earth–Ionosphere Cavity of Schumann Resonances - Gabriella Sátori; Earle Williams; Colin Price; Robert Boldi; Alexander Koloskov; Yuri Yampolski; Anirban Guha; Veronika Barta (Surveys in Geophysics, 2016)

Segmentation and Tracking of Marine Cellular Clouds observed by Geostationary Satellites - Alisa Gufan; Yoav Lehahn; Erick Fredj; Colin Price; Rachel Kurchin; Ilan Koren (International Journal of Remote Sensing, 2016)

Lightning Applications in Weather and Climate Research - Colin G. Price (Surveys in Geophysics, 2013)

A multinational study of neurological performance in antiretroviral therapy-naïve HIV-1-infected persons in diverse resource-constrained settings - Kevin Robertson; Johnstone Kumwenda; Khuanchai Supparatpinyo; Jeanne H. Jiang; Scott Evans; Thomas B. Campbell; Richard W. Price; Robert Murphy; Colin Hall; Christina M. Marra; Cheryl Marcus; Baiba Berzins; et al. (Journal of NeuroVirology, 2011)

Epidemiology of neuroendocrine cancers in an Australian population - Colin Luke; Timothy Price; Amanda Townsend; Christos Karapetis; Dusan Kotasek; Nimit Singhal; Elizabeth Tracey; David Roder (Cancer Causes & Control, 2010)

Secondary woody vegetation patterns in New Zealand's South Island dryland zone - Susan Walker; Nigel King; Adrian Monks; Sophie Williams; Larry Burrows; Ellen Cieraad; Colin Meurk; Jacob McC Overton; Robbie Price; Mark Smale (New Zealand Journal of Botany, 2009)
Can New Zealand's indigenous dryland ecosystems be rehabilitated by facilitating inherent successional tendencies to enhance development of indigenous‐dominated and often woody communities in the long term? Here, we describe the geographic distribution of woody communities of New Zealand's South Island drylands to generate hypotheses about successional trajectories to future vegetation states. Presences and absences of woody species in 3880 vegetation plots collated from past surveys were used to predict species potential distributions across drylands. Separate models and spatial predictions were built for each of four classes of woody richness, which were used as surrogates for successional stages. Woody species richness increased significantly from grassland to shrubland and from shrubland to forest cover, and trends in species traits also suggest richness class was related with successional stage. Indigenous woody species outnumbered exotic species in all richness classes. Assuming richness classes represent temporal progressions, our results suggest relatively homogeneous early‐successional woody associations succeed to a divergent array of woody associations in different environments. Growth forms of species in our predicted associations suggest transitions from grassland to tall, tree‐rich forests in northern and coastal drylands, and to liane‐rich open or lightcanopied shrubland, woodland, or low forest in more severe inland environments. These putative communities are novel in species composition but physiognomically broadly similar to pre‐settlement analogues. Especially in severe inland environments, unassisted transitions from grassland to indigenousdominated late‐successional woody communities may depend on the exclusion of tall exotic trees, Scotch broom, and gorse in early succession.

Structure–activity relationships in platinum–acridinylthiourea conjugates: effect of the thiourea nonleaving group on drug stability, nucleobase affinity, and in vitro cytotoxicity - Margaret C. Ackley; Colin G. Barry; Amanda M. Mounce; Michael C. Farmer; Beth-Erin Springer; Cynthia S. Day; Marcus W. Wright; Susan J. Berners-Price; Suzanne M. Hess; Ulrich Bierbach (JBIC Journal of Biological Inorganic Chemistry, 2004)

Interpretation of Roadside PM10 Monitoring Data from Sunderland, United Kingdom - Monica Price; Colin O'Dowd; Marion Dixon (Environmental Monitoring and Assessment, 2003)

Potential Impacts of Climate Change on Fire Regimes in the Tropics Based on Magicc and a GISS GCM-Derived Lightning Model - Johann Georg Goldammer; Colin Price (Climatic Change, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)